IDENTIFIKASI MODAL SOSIAL DAN MODAL INTELEKTUAL DALAM PENINGKATAN KEBERDAYAAN KELOMPOKTANI PADI SAWAH DI DESA EMPAT BALAI KECAMATAN KUOK KABUPATEN KAMPAR - Awan Setiawan; Ahmad Rifai; Kausar Kausar (Indonesian Journal of Agricultural Economics, 2022)
Social capital is a concept that is used to help rice farmers unite in achieving all common goals on the basis of togetherness and in which they are bound by structural, relational, and cognitive values. Intellectual Capital is a resource of information and knowledge that can function to improve competitiveness and improve farmer performance. The empowerment of lowland rice farmers is an effort made by lowland rice farmers in developing their abilities in the process of lowland rice farming. In a study entitled identification of social capital and intellectual capital in increasing the empowerment of lowland rice farmer groups in Empat Balai Village, Kuok District, Kampar Regency, the number of rice farmers sampled was 33 people consisting of core administrators in 11 farmer groups, with a sampling technique that is purposive technique. sampling. Based on the results of the study, the social capital variable has a result of 67.72 which is included in the medium category, the intellectual capital variable has a result of 72.25 which is included in the high category and the empowerment level variable has a result of 64.27 which is in the fairly empowered category